Powtórzenie w oryginale, powtórzenie w przekładzie - Magdalena Mitura (Ksiegarnia Akademicka Publishing, 2021)
Repetition in Original Work, Repetition in Translation: Remarks onthe Phenomenon of Repetition on the Example of Dukla by Andrzej Stasiuk and Its French Translation